Accuracy of the Provisional Prosthesis Scanning Techniqueversus a Conventional Impression Technique on Completely Edentulous Arches - Chunui Lee; Shavkat Dusmukhamedov; Yi-Qin Fang; Seung-Mi Jeong; Byung-Ho Choi (Applied Sciences, 2021)
Purpose: In this study, we aimed to compare the marginal fit of fixed dental restorations fabricated with the provisional prosthesis scanning technique versus a conventional impression technique and to determine the effect of both variables on the accuracy outcome. Materials and Methods: Twelve identical polyurethane edentulous maxillary models were equally divided into two groups: control (conventional impression group) and test (provisional prosthesis scanning group). After obtaining the impression using the above-mentioned methods and further preparing the final prosthesis, the passivity of the metal framework prosthesis was checked using a single screw test, i.e., only one screw was fixed on the terminal right abutment, and all others were empty. The marginal fit of the final prosthetic frameworks screwed onto the implants on the terminal left abutment was measured at the terminal right sight by periapical radiographs obtained immediately after metal framework placements in both groups. The medians derived from the two groups were compared using the Mann–Whitney test. In all tests, a p-value < 0.05 indicated statistical significance. Results: In the provisional prosthesis scanning group, the median marginal fit discrepancy was 170 µm (range 120–190). In the conventional impression group, the median marginal fit discrepancy was 1080 µm (range 1040–1100). There was a significant difference in the implant-framework marginal gap fit discrepancy between these two groups. Conclusion: Prostheses fabricated with the provisional prosthesis scanning technique are significantly more accurate than those fabricated with conventional impression techniques.